High-Porosity Foam-Based Iontronic Pressure Sensor with Superhigh Sensitivity of 9280 kPa−1 - Liu, Qingxian; Liu, Yuan; Shi, Junli; Liu, Zhiguang; Wang, Quan; Guo, Chuan Fei (Nano-Micro Letters, 2021)
Flexible pressure sensors with high sensitivity are desired in the fields of electronic skins, human–machine interfaces, and health monitoring. Employing ionic soft materials with microstructured architectures in the functional layer is an effective way that can enhance the amplitude of capacitance signal due to generated electron double layer and thus improve the sensitivity of capacitive-type pressure sensors. However, the requirement of specific apparatus and the complex fabrication process to build such microstructures lead to high cost and low productivity. Here, we report a simple strategy that uses open-cell polyurethane foams with high porosity as a continuous three-dimensional network skeleton to load with ionic liquid in a one-step soak process, serving as the ionic layer in iontronic pressure sensors. The high porosity (95.4%) of PU-IL composite foam shows a pretty low Young’s modulus of 3.4 kPa and good compressibility. A superhigh maximum sensitivity of 9,280 kPa−1 in the pressure regime and a high pressure resolution of 0.125% are observed in this foam-based pressure sensor. The device also exhibits remarkable mechanical stability over 5,000 compression-release or bending-release cycles. Such high porosity of composite structure provides a simple, cost-effective and scalable way to fabricate super sensitive pressure sensor, which has prominent capability in applications of water wave detection, underwater vibration sensing, and mechanical fault monitoring. Highlights: 1 High porosity and low modulus of the active layer are found to contribute to high sensitivity in a capacitive pressure sensor. 2 Pressure sensor achieves a superhigh sensitivity of 9280 kPa-1 by using polyurethane-ionic liquid foam with a high porosity (95.4%) and a low modulus (3.4 kPa).